Characterization of human umbilical cord blood mesenchymal stem cell-derived exosomes by size and zeta potential analysis - Dairov , Aidar; Issabekova , Assel; Kudaibergen , Gulshakhar; Ogay , Vyacheslav (Eurasian Journal of Applied Biotechnology, 2025)
Background: Exosomes are cup-shaped lipid bilayer extracellular vesicles with a diameter of 30– 200 nm, secreted by various cell types, including mesenchymal stem cells (MSCs) [1–3]. MSC- derived exosomes (MSC-Exo) play an important role in tissue regeneration and show therapeutic potential in psoriasis and other inflammatory, autoimmune, and degenerative diseases [3,4]. For exosome characterization, measurement of their size and zeta potential is essential, as these parameters provide key information about their stability and biological interactions [5]. This study aimed to characterize exosomes derived from human umbilical cord blood mesenchymal stem cells (hUCBMSC-Exo) by measuring their size and zeta potential. Materials and methods: Human umbilical cord blood MSC-derived exosomes (hUCB-MSC- Exo) were characterized by dynamic light scattering (DLS) and scanning electron microscopy (SEM). Particle size was measured using a NanoBrook 90Plus Zeta Analyzer (Brookhaven Instruments, USA) with three 15-minute runs at a 90° scattering angle. Zeta potential was determined using the same instrument equipped with a solvent-resistant electrode (BI-SREL) at 25 °C. For SEM, hUCB-MSC-Exo were coated with a 15 nm gold layer and examined using a Carl Zeiss Crossbeam 540 microscope (Carl Zeiss AG, Germany). High-resolution images were analyzed to determine particle size. Results: The average diameter of hUCB-MSC-Exo was 85.34 nm by DLS and 95.93 nm by SEM, both within the characteristic exosome size range (30–200 nm). The zeta potential ranged from −21.24 to −25.16 mV, indicating stable dispersion in solution and suggesting favorable interactions with target cell membranes due to the negative surface charge. Conclusion: The analyzed hUCB-MSC-Exo demonstrated size and surface charge consistent with typical exosomal characteristics, confirming the reliability of the applied methods for their physicochemical characterization. Funding: This research was supported by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan, grant No. AP13068269. Keywords: exosome, mesenchymal stem cell, characterization, size, zeta potential. References: Hade, M.D., Suire, C.N., Suo, Z. Mesenchymal stem cell-derived exosomes: applications in regenerative medicine. Cells 10, 1959 (2021). Gurung, S., Perocheau, D., Touramanidou, L., Baruteau, J. The exosome journey: from biogenesis to uptake and intracellular signalling. Cell Commun Signal 19, 47 (2021). Dairov, A., Issabekova, A., Ogay, V. Mesenchymal stem cell-derived exosomes in the treatment of skin and subcutaneous tissue diseases: a review. Curr Stem Cell Res Ther (2025) In press. Dairov, A., Sekenova, A., Alimbek, S., Nurkina, A., Shakhatbayev, M., Kumasheva, V., et al. Psoriasis: the versatility of mesenchymal stem cell and exosome therapies. Biomolecules 14, 1351 (2024). Gurunathan, S., Kang, M.-H., Jeyaraj, M., Qasim, M., Kim, J.-H. Review of the isolation, characterization, biological function, and multifarious therapeutic approaches of exosomes. Cells 8, 307 (2019).